2008
DOI: 10.1007/s10544-008-9185-4
|View full text |Cite
|
Sign up to set email alerts
|

Mixing behavior of the rhombic micromixers over a wide Reynolds number range using Taguchi method and 3D numerical simulations

Abstract: A planar micromixer with rhombic microchannels and a converging-diverging element has been systematically investigated by the Taguchi method, CFD-ACE simulations and experiments. To reduce the footprint and extend the operation range of Reynolds number, Taguchi method was used to numerically study the performance of the micromixer in a L(9) orthogonal array. Mixing efficiency is prominently influenced by geometrical parameters and Reynolds number (Re). The four factors in a L(9) orthogonal array are number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 23 publications
(34 reference statements)
0
20
0
Order By: Relevance
“…Smaller value of standard deviation means that the mixture is more homogenous and vice versa. The mixing efficiency is then calculated as in (5). Consequently, the value of mixing efficiency is 1 for completely mixing (100%) and is 0 for no mixing (0%).…”
Section: B Mixing Efficiency Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Smaller value of standard deviation means that the mixture is more homogenous and vice versa. The mixing efficiency is then calculated as in (5). Consequently, the value of mixing efficiency is 1 for completely mixing (100%) and is 0 for no mixing (0%).…”
Section: B Mixing Efficiency Evaluationmentioning
confidence: 99%
“…The authors in [5,6] propose planar passive micromixers with rhombic microchannels. These micromixers exploit the equal spitting and recombining of laminar flows to enhance the mixing efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Nimafar et al [4] carried out an experimental study to compare three SAR-type micromixers. Chung et al, [18] using simulations and experiments, investigated a planar rhombic micromixer with a converging-diverging element. They concluded that mixing is accomplished more quickly in their SAR design compared to T-and O-mixers at all flow rates.…”
Section: Introductionmentioning
confidence: 99%
“…Although active methods can achieve fast and effective mixing, they simultaneously complicate the fabricating process of microfluidic systems and need complex operations during the assay process [6]. Two passive micromixing concepts, namely split-recombine multilamination and chaotic advection, have been applied as passive micromixers [7,8]. Such passive micromixers are designed to promote an efficient diffusion with complex multilayer or three-dimensional (3D) microfluidic channels, either by increasing the interfacial area between fluids or by decreasing the distance over which diffusion takes place.…”
Section: Introductionmentioning
confidence: 99%